The impact of learning management systems in a virtual environment during the Covid-19 pandemic - Martínez Quezada, Ronald Ernesto
Nowadays, technology plays a crucial role in education by enabling the use of technological tools. So this work focuses on Learning Management Systems making known how technology has changed the world of education. Before the pandemic, these applications were not widely recognized, and only those who studied online had familiarity with some of these programs. This was because these tools were not commonly utilized in face-to-face classes. The year 2020 brought about significant changes as a result of the emergence of a new virus known as COVID-19. The virus had a profound impact on the way it spread, leading the government authorities to take drastic measures, including a nationwide quarantine. As a result, all educational institutions were ordered to close, and they had to adapt to online learning to ensure that students did not lose their academic year.The pandemic promoted the development of technological tools in education where new applications were created to improve online student learning. It allowed the continuity of classes virtually, and students and educators have had to adapt to this new mode of learning. For that reason, The Administration of Virtual Environments for Teaching and Learning Foreign Languages is a crucial course that helps students to effectively manage these tools and create educational web pages